The Structure of the Yom Kippur Discourse Unit: Discourse Analysis of Leviticus 16:1-34 (Impact: Journal of Transformation, 2022)
This paper applies discourse analysis to interpret Leviticus 16. Using a descriptive approach (not prescriptive), this study examined various discourse parameters which the author used in the composition of the Atonement Law. These include organizational structure, lexical repetition, boundary markers, regular and marked structures, discourse markers, participant reference, verbal structure/form, word order, and summary statements. These discourse parameters perform various functions such as enhancing cohesion, coherence, theme/topicalization, continuity and discontinuity, emphasis, and establishing the setting. The Yom Kippur discourse pericope and its seven significant divisions are established based on this examination. The divisions are Introduction (vv. 1-2a); Command for sacrificial animals and dress code (2b-5); Preliminary atonement procedures (vv. 6-10); Atonement procedures over the priests and the people (vv. 11-25); post-requisite atonement procedures (vv. 26-28); Command for the Day’s observance and cessation from work (vv. 29-34b), and the Conclusion (v. 34cd). It is also established that the fourth division (vss. 11-25) is prominent, for it is at the centre of the chiastic structure. By analyzing the Yom Kippur structure using the discourse analysis method, the unity of the Yom Kippur discourse has been defended. This means that every portion of the Atonement Law should be given the same weight in the interpretation. No part of the text is inferior to the other, for it is part of the larger whole. Also, what some other scholars have termed peculiarities, unnecessary repetitions, and inconsistencies in the chapter have been objectively explained. They are the author’s devices in achieving his communication purposes and not some evidence for suspicion of external interference of the original composition. Therefore, this study shows the suitability and applicability of the discourse analysis method in biblical studies in general.